2005
DOI: 10.1074/jbc.m500390200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Prion-dependent Polyglutamine Aggregation and Toxicity by Chaperone Proteins in the Yeast Model

Abstract: In yeast, aggregation and toxicity of the expanded polyglutamine fragment of human huntingtin strictly depend on the presence of the endogenous self-perpetuating aggregated proteins (prions), which contain glutamine/asparagine-rich domains. Some chaperones of the Hsp100/70/40 complex, modulating propagation of yeast prions, were also reported to influence polyglutamine aggregation in yeast, but it was not clear whether they do it directly or via affecting prions. Our data show that although some chaperone alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
108
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 59 publications
8
108
2
1
Order By: Relevance
“…Involvement of the Hsp70 chaperone system in yeast prion maintenance and curing is consistent with the finding that overexpression of Hsp70 suppresses polyglutamine-associated pathogenicity and reduces the formation of amyloid fibrils [97,98], and suggests that the Hsp70 family may have a universal role in suppressing the formation of pathogenic aggregates, including prions. However, to date, direct demonstration of an interaction between Hsp70 and yeast prions by in vitro biochemical analysis has not yet been reported.…”
Section: Chaperonessupporting
confidence: 67%
“…Involvement of the Hsp70 chaperone system in yeast prion maintenance and curing is consistent with the finding that overexpression of Hsp70 suppresses polyglutamine-associated pathogenicity and reduces the formation of amyloid fibrils [97,98], and suggests that the Hsp70 family may have a universal role in suppressing the formation of pathogenic aggregates, including prions. However, to date, direct demonstration of an interaction between Hsp70 and yeast prions by in vitro biochemical analysis has not yet been reported.…”
Section: Chaperonessupporting
confidence: 67%
“…As a first test of this idea, we found that 115-7c (100 M) did not alter the localization of Rnq1p-YFP, suggesting that prion status is unchanged by this treatment (supplemental ϩ status. Perhaps consistent with this general idea, the Chernoff Laboratory has observed that some chaperones impact polyQ toxicity through effects on prions, while others do not (48).…”
Section: Compound 115-7c Does Not Cure [Rnq1]mentioning
confidence: 74%
“…Another chaperone of the Hsp70 family, Ssb, consistently manifests itself as a [PSI ϩ ] antagonist (26). Hsp40 chaperones that act as co-chaperones of Hsp70s were shown to control propagation of [PIN ϩ ] (27) and modulate aggregation of heterologous poly(Q) proteins in yeast (28,29). Mechanisms of the chaperone effects on prions are not yet completely understood.…”
mentioning
confidence: 99%